Distinguishing Intrathyroid Parathyroid Adenoma from Colloid Nodules and Papillary Thyroid Carcinomas Using Multiphasic Multidetector Computed Tomography. Issue 5 (3rd September 2022) - Debnam, J. Matthew; Chi, T. Linda; Kwon, Michael; Sun, Jia; Schellingerhout, Dawid; Golant, Brandon T.; Ahmed, Salmaan; Perrier, Nancy D.; Vu, Thinh
Abstract : Objective: The aim of the study is to determine whether multiphase multidetector computed tomography (4D-MDCT) can differentiate between intrathyroid parathyroid adenomas (ITPAs), colloid nodules, and papillary thyroid carcinoma (PTC). Methods: We studied 22 ITPAs, 22 colloid nodules, and 11 PTCs in 55 patients. Hounsfield unit (HU) values of the nodules were measured on 4D-MDCT in the precontrast, arterial, venous, and delayed phases. Raw HU values, phase with peak enhancement, and washout percentages between the phases were evaluated. Results: Regardless of size, all ITPAs (22/22) showed peak enhancement in the arterial phase, which was significantly greater than both colloid nodules (15/22) and PTC (6/11, P = 0.002); thus, nodules with peak enhancement in the venous or delayed phase were not ITPAs (specificity = 1). For nodules with peak enhancement in the arterial phase, the percentage washout in the arterial-to-venous phases separated ITPAs from PTC and colloid nodules ( P < 0.001) with greater than or equal to 23.95% loss of HU value implying IPTA (area under curve, 0.79). This left a subset of colloid nodules or PTC that either peaked in the venous or delayed phase or had an arterial-to-venous phase washout of less than 23.95%. From this subset, PTC measuring 1 cm or greater could be separated from colloid based on HU values in the arterial phase with a cutoff HU value less than 81.4 for PTC (area under curve, 0.72) and an HU value greater than 164.5 suggested colloid. Conclusions: Intrathyroid parathyroid adenomas can be distinguished from colloid nodules and PTC by peak enhancement in the arterial phase and rapid washout. A subset of colloid and PTC measuring 1 cm or greater can be separated using arterial phase HU values.